Correction of refractive error in the adult population of Bangladesh: meeting the unmet need - Bourne, Rupert R A; Dineen, Brendan P; Huq, Deen M Noorul; Ali, Syed M; Johnson, Gordon J (Investigative ophthalmology & visual science, 2004)
To assess the extent of uncorrected refractive error and associated factors in Bangladesh and to suggest ways in which this need can be met. A nationally representative sample of 12,782 adults (>/= 30 years of age) was selected. Of them, 11,624 subjects underwent a demographic interview, visual acuity (logarithm of the minimum angle of resolution [logMAR]) measurement, automated refraction, and optic disc examination. Subjects with visual acuity less than 6/12 in either eye also had a corrected refraction measurement, cataract grading, and dilated retinal examination. Of the 11,624 subjects examined, 2,469 (22.1%) were myopes (less than -0.5 D) and 2,308 (20.6%) hyperopes (more than +0.5 D). The spectacle coverage percentage, calculated as [met need/(met need + unmet need) x 100%] was 25.2% and 40.5%, using 6/12 and 6/18 visual acuity cutoffs, respectively, and was higher in men and urban inhabitants. Older subjects and the literate and more highly educated were more likely to wear spectacles; however, most spectacle wearers (81%) had inadequate correction. Of the 1142 subjects who would benefit from spectacles, 827 (72.4%) would be suitable for off-the-shelf spectacles. Subjects without spectacles with less than 6/12 in the better eye (n = 835), would achieve 6/12 or better with correction (unmet need). Extrapolation to the national population yields an estimate that 1.5 million (6.7%) adult men and 1.8 million (9.2%) women have an unmet need for refractive correction. In Bangladesh, there is low spectacle coverage with a large unmet need. This survey identified risk groups, in particular women and those living in rural areas. This description of the availability of refractive services suggests areas for improvement (e.g., off-the-shelf spectacles) that may enable Bangladesh to achieve the goals of the World Health Organization's Vision 2020 initiative.